2019
DOI: 10.1016/j.envint.2019.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Human prenatal exposure to polychlorinated biphenyls (PCBs) and risk behaviors in adolescence

Abstract: Polychlorinated biphenyls (PCBs) are chemicals used in a variety of products before they were widely banned due to toxic effects in humans and wildlife. Because of continued persistence and ubiquity of these contaminants, risk of exposure to people living in industrialized countries is still high. Experimental research show that developmental exposure to PCB may alter function of brain pleasure centers and potentially influence disinhibitory behaviors, including tobacco and alcohol use. Yet, the potential effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Regarding alcohol consumption, TCDD seems not to affect alcohol consumption in mice with high and low alcohol preference [ 93 ]. In humans, prenatal exposure to polychlorinated biphenyls, some of which are in the dioxin family, appears to increase the risk of becoming tobacco and alcohol users [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding alcohol consumption, TCDD seems not to affect alcohol consumption in mice with high and low alcohol preference [ 93 ]. In humans, prenatal exposure to polychlorinated biphenyls, some of which are in the dioxin family, appears to increase the risk of becoming tobacco and alcohol users [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The organ coefficients of brains and testes were altered in male offspring, indicating that PCB118 exposure during fetal PGC migration had an impact on fetal development (Figure 2 and Figure 3). Studies have shown that prenatal exposure to PCBs can significantly alter the developmental processes of the fetal nervous and reproductive systems (Dickerson, Ransome, & Karlsson, 2019; Grandjean et al, 2012). Our present research indicated that PCB118 exposure in utero affected the reproductive health of male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…PolyChlorinated Biphenyls (PCBs) belong to a broad family of organic compounds exposure to which leads to health problems including cancer [ 61 , 62 ], endometriosis [ 63 ] and neurologic problems [ 64 , 65 ]. PCBs can pass through the placenta reaching the fetus but they can also be released in the human milk [ 66 ] and reach the newborn having significant toxicologic effects by interrupting the neurodevelopmental processes [ 67 ].…”
Section: Curcumin As Protector Of Cytotoxic and Teratogenic Agentsmentioning
confidence: 99%